Enhancing students' writing paragraphs through Canva Magic AI - Utami, Silvia; Karnedi, Karnedi (Universitas Muhammadiyah Purwokerto, 2024)
This research aimed to investigate the influence of Canva Magic AI on improving students' writing quality and to gauge their perceptions of using the tool. The study utilized a quantitative, pre-experimental One-Group Pretest–Posttest Design. Eight English literature students were selected using convenience sampling from an Intermediate English Grammar and Paragraph Writing class at STBA Persada Bunda during the 2023-2024 academic year. Data were collected via a writing test and a questionnaire. The findings revealed a significant improvement in students' writing quality after using Canva Magic AI, with a p-value of 0.012 from the Wilcoxon signed-rank test. Notable enhancements were observed across various writing components, including better organization, with more students receiving